Pengembangan Media Board Game Ular Tangga Berbasis Model SAVI untuk Meningkatkan Kemampuan Memahami Ide Pokok dalam Teks Nonfiksi Siswa - Anis Magfiroh; Nugraheti Sismulyasih SB (Paedagogie, 2026)
This research is based on the low ability of fourth-grade students at SDN Tambakaji 01 in identifying main ideas in non-fiction texts. The research aims to develop learning media in the form ofboard gamesnakes and ladders based on the SAVI model, while also testing its feasibility and effectiveness in improving these capabilities. The method used isResearch and Development(R&D) with reference to the Borg and Gall model which has been simplified into eight stages of development, namely: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trial, (7) product revision, and (8) usage trial. Data collection techniques were carried out through test and non-test techniques, tests include pretest and posttest, while non-tests include observation, interviews, questionnaire distribution, and documentation. The research subjects consisted of 6 class IV B students as samples in small group trials and 27 class IV A students as the population in large group trials. Data analysis techniques consisted of normality tests, N-gain tests, andpaired sample t-testThe results of the feasibility test show that the media obtained a rating percentage of 97.22.% from material experts and 98.07% from media experts with a very appropriate category. The results of the effectiveness test showed thatinthesmallgrouptest,thegain value was 0.6208, in the medium category, while in the large group test, it was 0.7209, in the high category. The t-test results showed a significance value of 0.000 < 0.05 with an average score of pretest of 58.78 with a completion percentage of 0% and an average score of posttest of  83.56 with a completion percentage of 88.89%. From the average results, a difference in scores was found pretest and posttest of 24.78% which means there is a significant difference between the results pretest and posttest. Thus, the mediaboard game the snakes and ladders game based on the SAVI model was declared feasible and effective for improving students ability to understand main ideas in non-fiction texts at SDN Tambakaji 01.